A cross-national comparison of the linkages between family structure histories and early adolescent substance use. (December 2022) - Stritzel, Haley; Green, Michael; Crosnoe, Robert
Abstract: Family structure can influence adolescent health with cascading implications into adulthood. Life course theory emphasizes how this phenomenon is dynamic across time, contextualized in policy systems, and grounded in processes of selection and socialization. This study used data from the U.S. (National Longitudinal Survey of Youth 1979 Child and Young Adults, n = 6, 236) and U.K. (Millennium Cohort Study, n = 11, 095) to examine associations between a single mother family structure between ages 0–14 and early adolescent substance use at age 14 across time and place, using inverse probability of treatment weighting to explore how results varied by selection into family structure. In both countries, single parenthood, regardless of its timing during childhood, consistently predicted adolescent substance use when samples were re-weighted to resemble the overall population. However, when samples were re-weighted so that their background characteristics resembled those of actual single parent families, there was little evidence that single parenting posed risks, suggesting that single parenting might matter less for adolescents who are likely to experience it (and vice versa). In addition, more generous welfare policy in the U.K. than in the U.S. did not appear to have ameliorated the observed role of single parenting in adolescent substance use. Findings supported a model of disadvantage saturation, where single parenting has little additional impact over the myriad other disadvantages that single parent families tend to experience, rather than a model of cumulative disadvantage, where single parenting compounds or adds to other disadvantages. Policy and interventions might more valuably focus on these other disadvantages than on family structure. Highlights: Living with a single mother was associated with early adolescent substance use. Associations were similar across the U.S. and U.K. and not differentiated by age. Single mother families were more risky to adolescents less likely to live in one. Findings were consistent with a disadvantage saturation model. Policy should focus on economic disadvantages associated with single parenthood.